2017
DOI: 10.1111/eci.12721
|View full text |Cite
|
Sign up to set email alerts
|

Study of the anti‐JCV antibody levels in a Spanish multiple sclerosis cohort

Abstract: Old age and HLA-DRB1*15:01 were the factors that influence positively and negatively, respectively, our anti-JCV antibody prevalence, although our both PML cases were HLA-DRB1*15:01carriers. Most of our patients showed a stable anti-JCV antibody index values during natalizumab treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 27 publications
(66 reference statements)
5
15
5
Order By: Relevance
“…It has been suggested that patients with an anti-JCV-antibody index >1.5 have an increased risk of the subsequent development of PML during natalizumab treatment 2. Data on natalizumab-treated patients pooled from large, open-label studies revealed that about 58% of patients were JCV seropositive3 and that 22–45% of patients in European countries had an index >1.5 45678…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that patients with an anti-JCV-antibody index >1.5 have an increased risk of the subsequent development of PML during natalizumab treatment 2. Data on natalizumab-treated patients pooled from large, open-label studies revealed that about 58% of patients were JCV seropositive3 and that 22–45% of patients in European countries had an index >1.5 45678…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it has to be distinguished whether the influence of the variable of interest (e.g., age) on either anti-JCV antibody status or index was investigated, and it has to be distinguished whether a cross-sectional study design (establishing an association between the variable of interest and anti-JCV antibody status or index) or a longitudinal study design (assessing the change over time, i.e., seroconversion/-reversion or change in anti-JCV AI) was applied. By cross-sectional design, higher anti-JCV antibody prevalence ( 5 , 10 17 ) and indices ( 4 , 6 ) were observed with increasing patients' age, as well as in most studies higher antibody prevalence in males ( 5 , 10 12 , 14 , 16 , 18 ). Prior use of DMTs had no impact on anti-JCV antibody positivity ( 11 14 , 16 , 17 ) and index ( 10 ).…”
Section: Discussionmentioning
confidence: 89%
“…By cross-sectional design, higher anti-JCV antibody prevalence ( 5 , 10 17 ) and indices ( 4 , 6 ) were observed with increasing patients' age, as well as in most studies higher antibody prevalence in males ( 5 , 10 12 , 14 , 16 , 18 ). Prior use of DMTs had no impact on anti-JCV antibody positivity ( 11 14 , 16 , 17 ) and index ( 10 ). By longitudinal design, age ( 4 ) and baseline anti-JCV AI ( 4 , 19 ) were predictors of later anti-JCV antibody serostatus change, whereas no influence of prior and current DMTs on seroconversion rate were observed ( 14 , 17 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A previous study reported that Scandinavian and German MS patients with anti-JCV antibodies had a significantly lower frequency of the human leukocyte antigen ( HLA ) -DRB1*15 haplotype than those without anti-JCV antibodies, suggesting the DRB1*15 haplotype is negatively associated with anti-JCV antibody positivity [ 13 ]. A recent Spanish study revealed that older age increased anti-JCV antibody positivity while HLA-DRB1*15:01 carriers had marginally lower anti-JCV antibody positivity rates than DRB1*15:01 non-carriers ( p = 0.056) [ 14 ]. These findings suggest that anti-JCV antibody serostatus are influenced by HLA class II alleles.…”
Section: Introductionmentioning
confidence: 99%